Historical biblical archaeology and the future the new pragmatism - Levy, Thomas Evan 1953- (London Oakville, CT Equinox Pub., 2010)
Into the future : new trends in historical biblical archaeology -- The new pragmatism : integrating anthropological, digital, and historical biblical archaeologies / Thomas E. Levy -- Re-constructing biblical archaeology : towards an integration of archaeology and the Bible / Shlomo Bunimovitz and Avraham Faust -- Future directions in the study of ethnicity in ancient Israel / Avi Faust -- Biblical archaeology as social action in Israel : two case studies / David Ilan -- The archaeology of the levant in North America : the transformation of biblical and Syro-Palestinian archaeology / Aaron Burke -- Some applications -- Biblical archaeology and egypt during the EB III and EB IV : new connections / Miroslav Barta -- New perspectives on Levantine Mortuary ritual : a cognitive interpretive approach to the archaeology of death / Aaron Brody -- Under the shadow of the four-room house : biblical archaeology meets household archaeology in Israel / Assaf Yasur-Landau -- The Philistines and their material culture in context : future directions of historical biblical archaeology for the study of cultural transmission / Ann Killebrew -- Judha, Masos, and Hayil : the importance of etnohistory and oral traditions / Eveline J. van der Steen -- Four chronological anchors of the low chronology in historical biblical archaeology : an appraisal / Daniel A. Frese, Thomas E. Levy, and Thomas Higham -- From text to turf -- Texts in exile : towards an anthropological methodology for incorporating texts and archaeology / Tara Carter and Thomas E. Levy -- Excavating the text of 1 Kings 9 : the gates of Solomon / William Schniedewind -- Culture, memory, and history : reflections on method in biblical studies / Ronald Hendel -- Archaeology, the Bible, and history : the fall of the House of Omri and the origins of the Israelite state / Baruch Halpern -- Integrating archaeology and texts : the example of the Qumran toilet / Jodi Magness -- In perspective -- Stones, bones, texts, and relevance or how I lost my fear of biblical archaeology and started enjoying it / Aren Maeir -- A Bible scholar in the City of David / Richard Elliott Friedman -- Books and stones and ancient Jewish history : a view from Camp David / David Goodblatt -- The archaeology of Palestine in the post-biblical periods : the intersection of text and artifact / Jodi Magness -- The changing place of biblical archaeology, exceptionalism or normal science / Alexander H. Joffe -- Does biblical archaeology have a future? / William G. Dever
Does biblical archaeology have a future? William G. Dever.
Includes bibliographical references and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Antiquities; Bible -- Antiquities; Aufsatzsammlung